Mapping Intellectual Building and the Construction of Thought and Reason - Hassan Malkawi, Fathi (International Institute of Islamic Thought, 2020)
The subject of this work is thought, a distinguishing characteristic of human beings that the Creator has dignified humankind with. The book attempts to provide an in-depth conceptualization of intellectual building. Man's intellect is awoken by his/her surroundings, by his need to make sense of reality, his own existence, and a desire to know. How he articulates this reality to himself, interprets, and organizes information as it presents itself to his conscience, makes decisions, takes action, and draws conclusions based on whatever framework he gives value to, whether spiritual or other, is the subject of this book. The work reflects on many interesting aspects of human inner communication, including the workings of logic, and in today's information age, the control and manipulation of information by others for personal gain. What is meant by the concept of 'thought'? What place does it hold, and in what relation does it stand to the concepts of knowledge, culture, philosophy, literature, and fiqh (deep understanding, jurisprudence)? These are some of the issues addressed.